Sustainability Delivered - Pullman, Madeleine (Business Expert Press, 2012)
Ebook from IG Library ; If you are a supply chain manager, an executive, an entrepreneur, or a stakeholder in a sustainable business, this book will help you develop the awareness and skills needed to support sustainable supply chain management in your firm. The authors introduce the many ways that social and environmental responsibility can be integrated into supply chain management, from sustainable product and process design to programs and techniques that support product end-of-life management. The book begins with a discussion of sustainability and business strategy. It then explores product and process design.